2020
DOI: 10.21203/rs.3.rs-53397/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Exclusive Breast Feeding Practice among HIV Positive Mothers in North East Ethiopia: A mixed method study

Abstract: Background: Exclusive breast feeding (EBF) of Human Immune Virus (HIV) exposed infants for the first six months is strongly recommended and vital for protecting them against common childhood illnesses including diarrhea and pneumonia. Despite its benefit, EBF practice is low in developing countries including Ethiopia. There is a paucity of evidence for factors associated with EBF among HIV positive mothers. Objectives: To assess exclusive breast feeding practice and its associated factors among HIV positive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There is a renewed commitment by different stakeholders on ending the burden of undernutrition. The adoption of the Sustainable Development Goals (SDGs), the United Nations’ proclamation of a Decade of Action on Nutrition (2016–2025) and the Rome Declaration on Nutrition and the Framework for Action in the year 2014 by world leaders, suggested that well thought out and clear-cut actions are needed to tackle undernutrition [ 16 ]. Addressing undernutrition in all its forms will play a significant role in achieving goals 1 to 3 of the SDGs and other global targets relating to non-communicable diseases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a renewed commitment by different stakeholders on ending the burden of undernutrition. The adoption of the Sustainable Development Goals (SDGs), the United Nations’ proclamation of a Decade of Action on Nutrition (2016–2025) and the Rome Declaration on Nutrition and the Framework for Action in the year 2014 by world leaders, suggested that well thought out and clear-cut actions are needed to tackle undernutrition [ 16 ]. Addressing undernutrition in all its forms will play a significant role in achieving goals 1 to 3 of the SDGs and other global targets relating to non-communicable diseases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, undernutrition was highest among nulliparous women (34%) followed by in women with six or more children (30%). 24 Similarly, a study in Bangladesh found that the risk of being underweight was higher among young mothers who had more than two children compared to their counterparts. 25 A similar result was observed among women in Western China where the odds of having chronic energy deficiency was higher with high parity.…”
Section: Individual-level Factorsmentioning
confidence: 99%
“…Married women had the lowest prevalence of undernutrition while the prevalence was highest, at 36%, among women who had never married, 32% among widows and 29% among divorced women; the odds of being malnourished were 1.9 times higher in women who had never married than in currently married women (p-value < 0.001). 24 Figure 1. A conceptual framework for analysing the causes of malnutrition in women of reproductive age in Nigeria.…”
Section: Individual-level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have utilised the MDD-W measure to find a strong link between improved dietary diversity and health outcomes ( 6 , 9 – 11 ) . Evidence also suggests that there are many determinants of improved dietary diversity for women with different contextual factors playing an important role in women’s food consumption ( 9 , 12 , 13 ) .…”
mentioning
confidence: 99%